2002
DOI: 10.1038/sj.cgt.7700415
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of murine mammary carcinoma growth and metastasis by HSVtk/GCV gene therapy using in vivo electroporation

Abstract: The effectiveness of electroporation as a means of gene transfection, both in vitro and in vivo, was tested using the herpes simplex virus 1 thymidine kinase (HSVtk) gene in combination with ganciclovir (GCV) administration as therapy against murine mammary cancer. Approximately 80% of BJMC3879 metastatic mammary carcinoma cells, derived from MMTV-infected BALB/c mice, died as a result of HSVtk/GCV treatment 72 hours after the transfection; decreased DNA synthesis was also seen. Mammary tumors induced by inocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 21 publications
1
51
0
Order By: Relevance
“…11 We have further shown that HSVtk/GCV therapy strongly suppresses metastasis in a murine metastatic mammary cancer model. 13 Gene transfer by in vivo electroporation (electrogene transfer) has recently been found to be an effective method for introducing DNA into various tissues. [14][15][16][17] Although previously believed to have a very low transfection efficiency, it was recently reported that, under suitable conditions, transduction is approximately equivalent to that using an adenoviral vector concentration of 10 6 transduction U/ml.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 We have further shown that HSVtk/GCV therapy strongly suppresses metastasis in a murine metastatic mammary cancer model. 13 Gene transfer by in vivo electroporation (electrogene transfer) has recently been found to be an effective method for introducing DNA into various tissues. [14][15][16][17] Although previously believed to have a very low transfection efficiency, it was recently reported that, under suitable conditions, transduction is approximately equivalent to that using an adenoviral vector concentration of 10 6 transduction U/ml.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental gene therapy using in vivo electroporation has, in fact, recently been demonstrated to effective in several animal tumor models, for colon adenocarcinomas, 19 melanomas, 20 hepatocellular carcinomas, 21 urinary bladder carcinomas 22 and mammary adenocarcinomas. 13,23,24 Here, we conducted an antiangiogenic gene therapy trial using electrogene transfer of endostatin in a mouse metastatic mammary cancer model having a metastatic spectrum similar to that seen in human breast cancers. As a paramount challenge for antiangiogenic therapy is to design combination protocols that counteract angiogenic stimuli produced by the tumor cells and induce direct/indirect cytotoxicity, we also tried combination gene therapy of endostatin and HSVtk/GCV using electrogene transfer.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, gene transfer by in vivo electroporation, a procedure that involves DNA injection followed by application of electric fields, is effective for introducing DNA into mouse muscle, 26 skin, 27 rat liver, 28 and tumors. 19,29 Earlier data show that use of in vivo electroporation enhances plasmid DNA uptake in tumor tissue, resulting in expression within the tumor. [30][31][32][33] Furthermore, in vivo electroporation is a safe and nontoxic delivery system.…”
Section: Discussionmentioning
confidence: 99%
“…Ganciclovir was added at a concentration of 50 mmol and cells were exposed for 72 hours. [22][23][24] Construction of EGFP expressing leukemia cell lines Construction, expansion and purification of the EGFP expressing retrovirus has been described previously. 25 Amphotropic retrovirus was harvested from the supernatant of the packaging cell line RetroPack PT67 (Clontech).…”
Section: Cells and Cell Transfectionsmentioning
confidence: 99%